Semiotic Analysis in the Lyrics of the Song Tikus-Tikus Kantor and Its Significance for Fraud Accounting Actors - Ardimansyah; Rafles Ginting; Elga Yulindisti; Anton Robiansyah; Rissa Anandita (Universitas Negeri Semarang, 2024)
The role of the song